Measurement of perceived psychological safety: Integration, review and evidences for the scale in the context of Turkey - BÜLBÜL, SEÇİL (My University, 2022)
Psychological safety can predict many positive individual and organizational outcomes at work, and previous research addressed how psychological safety contributes to positive work attitudes and behaviors. In Turkey, there is quite an amount of research showing the contributing role of psychological safety perception on employees\" positive performance behaviors and organizational effectiveness and innovativeness. However, previous research in Turkey does not adequately show the reliability and validity of the psychological safety scale, which was developed by Edmondson (1999). Based on the suggested requirement this study aimed to investigate the psychological safety perceptions of individuals who work in various sectors in Turkey. The adapted version of the psychological safety scale was used to gain evidence for the reliability and validity of the instrument in Turkey. In total, 585 individuals working in various industries and from various occupational groups participated in the research. Both exploratory factor analysis and the confirmatory factor analysis showed that Turkish adapted version of the psychological safety scale was valid and reliable.
Keywords: SOSYOLOJİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); SOCIOLOGY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Psychological Safety; Scale Reliability; Scale Validity; Turkey; EMPLOYEE VOICE; LEADERSHIP; KNOWLEDGE; BEHAVIOR; PERFORMANCE; QUALITY